Collaborative communicative tasks : interacting in an EFL blended learning class. (2021)
This document presents a pedagogical and didactic innovation proposal which aims to implement collaborative communicative tasks to encourage oral interaction through using ICT tools in an EFL blended classroom. This proposal is directed at tenth graders whose ages range from 15 to 18 years old from public schools in Colombia. Based on the analysis of several research studies conducted not only in Colombia, but also overseas, and the design of 3 cycles of intervention with their corresponding materials; implications, limitations and conclusions could be identified regarding the development of this pedagogical innovation proposal.